Discovery of a potent microtubule-targeting agent: Synthesis and biological evaluation of water-soluble amino acid prodrug of combretastatin A-4 derivatives. Issue 11 (1st June 2015) - Yu, Kun; Li, Rong; Yang, Zhuang; Wang, Fang; Wu, Wenshuang; Wang, Xiaoyan; Nie, Chunlai; Chen, Lijuan
Graphical abstract: Abstract: Amino acid prodrugs are known to be very useful for improving the aqueous solubility of sparingly water soluble drugs ( Drug Discovery Today 2013, 18, 93). Therefore, we synthesized eleven novel combretastatin A-4 amino acid derivatives and evaluated their anti-tumor activities in vitro and in vivo. Among them, compound15 (valine attached to compound3, which was shown to be a potent tubulin polymerization inhibitor in our previous study) exhibited high efficacy in tumor-bearing mice, and pharmacokinetic analysis in rats indicated that compound15 was an effective prodrug as well. Besides, compound15 significantly inhibited tubulin polymerization in vitro and in vivo by binding to the colchicine binding site. In addition, compound15 induced cell cycle arrest in the G2/M phase and triggered apoptosis in a caspase-dependent manner. In conclusion, our study showed that compound15 could have significant anti-tumor activity as a novel microtubule polymerization disrupting agent with improved aqueous solubility.